The Performance of Islamic Bank in Terms of Human Resources, Outstanding Loans, and NPF: Mann-Whitney Analysis - I Nyoman Budiono; Hartina Husain; St. Nurhayati; Syahruddin Kadir; Nurul Fauzia; Nurul Muhlisa (Universitas Bina Sarana Informatika, 2026)
Sharia banks act as financial institutions that perform financial intermediary functions, connecting parties with excess funds with parties in need of funds. The pandemic era in early 2020 is one of the most striking examples that shows the serious impact of macroeconomic changes on Islamic banking in Indonesia. This study focuses on the performance of Islamic banking. It aims to analyze changes in four variables: number of branches, number of human resources, outstanding financing, and Non-Forming Finance in Islamic banks, both before and during the pandemic. The method used is a statistical approach sourced from secondary data published by the OJK, which includes a sample of 12 Islamic commercial banks and 21 Islamic business units. The analysis technique used is a descriptive comparative analysis of the results of the Mann-Whitney statistical test. The results of this study, based on the analysis using the Mann-Whitney test, indicate significant differences in these variables between the periods before and during the COVID-19 pandemic in the Islamic banking sector. Therefore, a strategic response is needed from the Islamic banking sector in addressing changes in the economic situation and customer behavior influenced by external factors such as the pandemic. The importance of adaptation by the Islamic banking sector in facing a pandemic, as well as the importance of better risk management in managing business growth and credit risk.